2021
DOI: 10.3390/agriculture11100955
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Feeding a High Calcium: Phosphorus Ratio, Phosphorous Deficient Diet on Hypophosphatemic Rickets Onset in Broilers

Abstract: Recently, a P-deficient diet caused rickets in commercial chicks within three days. This study aimed to investigate the duration of onset of rickets in chicks. Data were collected from 3–11 day old chicks raised on 88 commercial farms. Male day-old Arbor Acres Plus broilers (n = 450) were studied in three trials, with three to four treatments each. Each treatment used one of the following crumbled feeds: control feed (calcium (Ca): phosphorus (P)-1.41), slightly high Ca:P feed (SHCa:P, Ca:P-2.69), high Ca:P ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Li et al (2012) noted that the body weight, weight gain and feed intake were reduced by high calcium-to-phosphorus ratio. Xu et al (2021) observed that the levels of lameness and rickets increased in birds fed a low phosphorus diet especially when the Ca-to-AvP ratio was unbalanced (a high Ca:P ratio), whereas, birds fed a low phosphorous diet with a balanced Ca:P ratio recorded optimal growth performance and a healthy bone structure.…”
Section: Body Weight Gain and Feed Conversion Ratiomentioning
confidence: 96%
“…Li et al (2012) noted that the body weight, weight gain and feed intake were reduced by high calcium-to-phosphorus ratio. Xu et al (2021) observed that the levels of lameness and rickets increased in birds fed a low phosphorus diet especially when the Ca-to-AvP ratio was unbalanced (a high Ca:P ratio), whereas, birds fed a low phosphorous diet with a balanced Ca:P ratio recorded optimal growth performance and a healthy bone structure.…”
Section: Body Weight Gain and Feed Conversion Ratiomentioning
confidence: 96%
“…Nutritional deficiencies can affect broiler chickens weight and weight gain by interfering with their ability to grow and develop their skeletons (Ventura and Matias da Silva, 2019). A study by Xu et al (2021) showed that body weight and weight gain were affected by dietary calcium and phosphorus deficiency, causing a reduction in both parameters.…”
Section: Growth Performancesmentioning
confidence: 99%
“…The amount of phosphorus in the diet is also under debate. However, a P-deficient diet caused rickets in commercial chicks within three days [4]. There is constant pressure from pathogens and new threats, such as avian flu, that require new treatments and biosecurity measures.…”
mentioning
confidence: 99%